Pengaruh Lama Perendaman dan Jenis Pembungkus terhadap Kadar Etanol Tape Ketan (Universitas Negeri Semarang, 2022)
Tape is one of the traditional foods in Indonesia which is produced through the fermentation process of carbohydrate foods. This study aims to determine the effect of the different packaging and cooking methods on the organoleptic properties and ethanol content of sticky rice tape. The research method used experimental research methods using a completely randomized design with a factorial pattern. The first factor is soaking time, which is soaked for 3 hours before cooking (T1) and without soaking before cooking (T2). The second factor is the type of wrapping, namely banana leaf (L1), plastic container (L2), and water guava leaf (L3). Each treatment method of cooking and wrapping was varied again by being given dragon fruit juice, pineapple juice, and without the addition of fruit juice. Parameters tested include organoleptic and ethanol content. The results of the organoleptic assessment of glutinous tape ranged from 7.00-8.47. The ethanol content of sticky rice tape soaked before cooking and wrapped in banana leaves was 2,936-15.879%; wrapped in 3,974-14,408% plastic containers, 6,464-16,181% guava leaves wrapped. Glutinous tape without soaking before cooking and wrapped in banana leaves 1.747-10.219%, wrapped in plastic containers 3.879-12.276%, wrapped in guava leaves 3.936-6.577%. Based on the organoleptic assessment and the ethanol content, the best quality tape and preferred by consumers is the original glutinous rice tape through the cooking process by soaking it and wrapping it in banana leaves. The appearance of the tape is whole, fresh white, the texture is soft and watery, has a very fresh aroma specific to the tape, it also has a slightly sweet taste, slightly sour, and contains 2.936% ethanol. Tape merupakan salah satu makanan tradisional di Indonesia yang dihasilkan melalui proses fermentasi bahan pangan berkarbohidrat. Penelitian ini bertujuan untuk untuk menentukan pengaruh pembungkus dan cara memasak yang berbeda terhadap sifat organoleptik dan kadar etanol tape ketan. Metode penelitian menggunakan metode penelitian eksperimental dengan menggunakan rancangan acak lengkap (RAL) pola faktorial. Faktor pertama adalah lama perendaman, yaitu direndam selama 3 jam sebelum dimasak (T1) dan tanpa direndam sebelum dimasak (T2). Faktor kedua adalah jenis pembungkus, yaitu daun pisang (L1), wadah plastik (L2), daun jambu air (L3). Setiap perlakuan cara memasak dan pembungkus, divariasi lagi dengan diberi sari buah naga, sari buah nanas, dan tanpa penambahan sari buah. Parameter yang diuji meliputi organoleptik dan kadar etanol. Hasil penilaian organoleptik tape ketan berkisar 7,00-8,47. Kadar etanol tape ketan dengan direndam sebelum dimasak dan dibungkus daun pisang yaitu 2,936-15,879%; dibungkus wadah plastik 3,974-14,408%, dibungkus daun jambu 6,464-16,181%. Tape ketan tanpa direndam sebelum dimasak dan dibungkus daun pisang 1,747-10,219%, dibungkus wadah plastik 3,879-12,276%, dibungkus daun jambu 3,936-6,577%. Berdasarkan penilaian organoleptik dan kadar etanol, kualitas tape yang paling baik dan disukai konsumen adalah tape ketan original melalui proses memasak dengan direndam dan dibungkus dengan daun pisang. Kenampakan tape utuh, putih segar, teksturnya lunak dan berair, mempunyai aroma sangat segar spesifik tape, juga mempunyai rasa agak manis, sedikit asam dan mengandung kadar etanol 2,936 %. Tambahkan aspek kebaruan dari hasil penelitian ini (termasuk dalam abstract). Keywords: Ethanol, Wrapping Media, Soaking, Glutinous Tape Kata kunci: Etanol, Media Pembungkus, Perendaman, Tape Ketan